Census Tract Data, 1940: Elizabeth Mullen Bogue File - Bogue, Donald ([Verlag nicht ermittelbar], 2000)
The 1940 Census Tract files were originally created by keypunching the data from the printed publications prepared by the Bureau of the Census. The work was done under the direction of Dr. Donald Bogue, whose wife, Elizabeth Mullen Bogue, completed much of the data work. Subsequently, the punchcards were converted to data files and transferred to the National Archive and Records Administration (NARA). ICPSR received copies of these files from NARA and converted the binary block length records to ASCII format.